Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Public understanding of sustainable diets and changes towards sustainability: A qualitative study in a UK population sample - B. Whittall; S.M. Warwick; D.J. Guy; K.M. Appleton (Appetite, 2023)

Costs, benefits, and fitness consequences of different migratory strategies - José A. Alves; Tómas G. Gunnarsson; Daniel B. Hayhow; Graham F. Appleton; Peter M. Potts; William J. Sutherland; Jennifer A. Gill (Ecology, 2013)
The relative fitness of individuals across a population can shape distributions and drive population growth rates. Migratory species often winter over large geographic ranges, and individuals in different locations experience very different environmental conditions, including different migration costs, which can potentially create fitness inequalities. Here we used energetics models to quantify the trade‐offs experienced by a migratory shorebird species at locations throughout the nonbreeding range, and the associated consequences for migratory performance, survival, and breeding habitat quality. Individuals experiencing more favorable winter conditions had higher survival rates, arrived on the breeding grounds earlier, and occupied better quality breeding areas, even when migration costs are substantially higher, than individuals from locations where the energy balance on the wintering grounds was less favorable. The energy costs and benefits of occupying different winter locations can therefore create fitness inequalities which can shape the distribution and population‐wide demography of migratory species.

Characterisation of 22 polymorphic microsatellite loci for the Broadbill Swordfish, Xiphias gladius - H. Bradman; P. Grewe; J. Bourjea; D. Muths; B. Appleton (Conservation Genetics Resources, 2011)

Nitrogen Phytoremediation by Water Hyacinth (Eichhornia crassipes (Mart.) Solms) - L. J. Fox; P. C. Struik; B. L. Appleton; J. H. Rule (Water, Air, & Soil Pollution, 2008)

The role of antioxidants in models of inflammation: Emphasis on l-arginine and arachidonic acid metabolism - M. Kapoor; A. N. Clarkson; B. A. Sutherland; I. Appleton (Inflammopharmacology, 2005)